DETERMINANTS OF FAST FOOD CONSUMPTION AND PREFERENCES AMONG UNDERGRADUATE STUDENTS OF AHMADU BELLO UNIVERSITY, ZARIA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
The study was carried out to determine the factors affecting fast food consumption among Ahmadu Bello University, Zaria students. Primary Data from 240 students from four faculties collected through a multi-stage sampling procedure using a structured interview schedule were used for data analysis. The data was analyzed using descriptive statistics and a double hurdle regression model. The result shows that 52% of student expenditure per semester was allotted to fast food and lunch constituted 36.9% of total fast food expenditure. Snacks, noodles (popularly known as Indomie) and fried rice were the mostly consumed fast food with the value of 29.9%, 24.2%, and 12.8% respectively. The pooled results indicates that the factors that influence the students’ decision to consume fast food shows slight variation from those influencing level of consumption and where it does, not by the same magnitude and direction. For instance, age (p
Keywords: Budget share, double hurdle, expenditure, fast foo